Salted egg agroindustry in Brebes during the covid-19 pandemic - Muhamad Hasdar; Ludfia Windyasmara (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
This study aims to describe changes in the agro-industrial activities of salted eggs in Brebes Regency during the Covid-19 pandemic, both in marketing and agro-industrial processes. This research was conducted from January to April 2021. A total of 135 active salted egg agroindustries located in 12 sub-districts of 17 subdistricts in Brebes Regency were applied in this study. The research sample was 50 industries determined by purposive random sampling, namely districts with the most significant number of salted egg agroindustries (Brebes, Bulakamba, and Warnasari Regencies). Respondents are the owners of salted egg agroindustries who were selected as samples. Primary data (marketing distribution of salted eggs and salted egg processing technology) were collected by interview using a questionnaire and observation. Secondary data were collected by recording related documents from the government and the Central Bureau of Statistics of Brebes Regency. Data on the distribution of egg processing technology was analyzed descriptively. During the Covid-19 pandemic, producers had difficulty obtaining raw materials during a pandemic which triggered a 59% decline in salted egg production followed by a decrease in demand. Changes in salting salted eggs did not occur during the Covid-19 pandemic despite a decline in production. Salted egg producers do not reduce the quality of the salting method. As many as 30% of salted egg producers produce a combination of original, grilled, and baked flavors.